...but good news for Fijians sugar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
In anticipation of an official declaration by Mauritius which would confirm its production losses and its quota shortfall of 90,000 tonnes, Fiji was preparing to sell part of its output to the European Union for more than three times the world...